(3GdEfLjds
(3ChdgG (B:s
(3bOehG Edjg EfSGf CUe eLfhf aEPG CNQL GdTjWGf fWb aYLH GdLeY bGHdjf de jXgQ bW eKd gPG ai Bd ESQGFjd s
(3BNQgG (B:s
(3hGdJi di cdgG dc ceG Cfi CfG dSJ ef GdYGde s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B175s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdOjGfGJ GdCNQis